Super-Recognizers – a novel diagnostic framework, 70 cases, and guidelines for future work. (30th July 2021) - Ramon, Meike
Abstract: When you hear the word Super-Recognizer, you may think of comic-book-hero-esque agents searching the underground to find people who went missing decades ago. Compared to this fantasy, the reality seems somewhat less exciting. Super-Recognizers (SRs) were initially reported a decade ago as a collateral while developing tests for developmental prosopagnosia. Today, the topic of SRs sparks interest from groups seeking to enhance scientific knowledge, public safety, or their monetary gain. With no immediate consequences of erroneous SR identification, there has been no pressure to establish a clear SR definition. This promotes heterogenous empirical evidence and the proliferation of unsupported claims in the media. Not only is this status quo unfortunate, it stands in opposition to the potential of special populations – both for science and application. SRs are a special population with imminent real-world value that can advance our understanding of brain functioning. To exploit their potential, I propose a needed formal framework for SR diagnosis, and introduce 70 cases identified based hereupon. These cases represent the core of a growing SR cohort, studied in my lab in the course of a long-term, multi-methodological research agenda involving academic and government collaborators. Finally, I provide recommendations for those interested in SR work, and highlight current caveats and future challenges.